2021
DOI: 10.1002/vetr.1118
|View full text |Cite
|
Sign up to set email alerts
|

Effect of topical non‐steroidal anti‐inflammatory drugs on healing times and complications in dogs with spontaneous chronic corneal epithelial defects

Abstract: Background: Little is published regarding topical NSAID effect on corneal healing in dogs. This retrospective cohort study aimed to compare healing times and complications in dogs with spontaneous chronic corneal epithelial defects (SCCED) treated with and without topical non-steroidal antiinflammatory drugs (NSAID). Methods: Medical records of 66 dogs (71 eyes) diagnosed with SCCED between 2008 and 2019 were included. Eyes were divided into: (1) those receiving topical NSAIDs (n = 33) versus (2) those not rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Recent studies have shown varied outcomes regarding the use of topical ketorolac in the context of wound healing post‐cataract surgery. Some studies suggest that ketorolac may delay healing due to its inhibition of prostaglandin synthesis, which is essential for the initiation of the healing process 6 . Conversely, other research indicates that ketorolac does not adversely affect wound healing and may, in fact, contribute to a more favourable postoperative course by controlling inflammation effectively 7 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown varied outcomes regarding the use of topical ketorolac in the context of wound healing post‐cataract surgery. Some studies suggest that ketorolac may delay healing due to its inhibition of prostaglandin synthesis, which is essential for the initiation of the healing process 6 . Conversely, other research indicates that ketorolac does not adversely affect wound healing and may, in fact, contribute to a more favourable postoperative course by controlling inflammation effectively 7 …”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggest that ketorolac may delay healing due to its inhibition of prostaglandin synthesis, which is essential for the initiation of the healing process. 6 Conversely, other research indicates that ketorolac does not adversely affect wound healing and may, in fact, contribute to a more favourable postoperative course by controlling inflammation effectively. 7 Given these conflicting reports, a systematic examination and synthesis of available data are necessary to provide clarity on the effects of topical ketorolac on wound healing post-cataract surgery.…”
mentioning
confidence: 99%